2012
DOI: 10.1111/j.1365-2052.2012.02358.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeography and genetic diversity of East Asian goats

Abstract: The domestic goat is one of the most important livestock species, but its origins and genetic diversity still remain uncertain. Multiple highly divergent maternal lineages of goat have been reported in previous studies. Although one of the mitochondrial DNA lineages, lineage B, was detected only in eastern and southern Asia, the geographic distribution of these lineages was previously unclear. Here, we examine the genetic diversity and phylogeographic structure of Asian goats by mitochondrial DNA sequences and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 16 publications
3
32
0
Order By: Relevance
“…In addition, it was proven that at least one subclade of lineage B was originated from eastern Asia, especially in southwest China [36]. Some studies also support the hypothesis that the southwest of China might be one of the domestication centers [37], [38].…”
Section: Discussionmentioning
confidence: 95%
“…In addition, it was proven that at least one subclade of lineage B was originated from eastern Asia, especially in southwest China [36]. Some studies also support the hypothesis that the southwest of China might be one of the domestication centers [37], [38].…”
Section: Discussionmentioning
confidence: 95%
“…Previous molecular studies using mtDNA D‐loop region were performed to investigate the origin and genetic relationship of goats (Chen, Su, Wu, Sha, & Zhang, ; Fernandez et al., ; Joshi et al., ; Lin et al., ; Luikart et al., ; Mannen, Nagata, & Tsuji, ; Naderi et al., ; Sultana, Mannen, & Tsuji, ). These studies revealed six highly divergent lineages of goat mtDNA (haplogroups A–G).…”
Section: Introductionmentioning
confidence: 99%
“…These studies revealed six highly divergent lineages of goat mtDNA (haplogroups A–G). Haplogroup A is distributed worldwide (Naderi et al., ), whereas most animals in haplogroup B are primarily found in South and Southeast Asia, with their frequency tending to increase southeastward (Lin et al., ). Haplogroup C is found in Asia and Europe with low frequencies, and the minor haplogroups D, F, and G are observed in Asia, Sicily, and the Near East and northern Africa, respectively, at low frequencies (Naderi et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, the global diversity of local goats has been assessed using various molecular tools, and such studies have been conducted in Spain (Ferrando et al., ; Manunza et al., ), Africa (Awotunde et al., ; Kibegwa, Githui, Jung'a, Badamana, & Nyamu, ; Mdladla, Dzomba, Huson, & Muchadeyi, ), the Americas (Carvalho, Paiva, Araújo, Mariante, & Blackburn, ), Europe (Bulut, Kurar, Ozsensoy, Altunok, & Nizamlioglu, ; Windig et al., ), and Asia (Lin et al., ; Nicoloso et al., ; Waki, Sasazaki, Kobayashi, & Mannen, ; Yadav, Gahlot, Gahlot, Asraf, & Yadav, ).…”
Section: Introductionmentioning
confidence: 99%